2021
DOI: 10.3390/biomedicines10010024
|View full text |Cite
|
Sign up to set email alerts
|

Discovery Potent of Thiazolidinedione Derivatives as Antioxidant, α-Amylase Inhibitor, and Antidiabetic Agent

Abstract: This work aimed to synthesize safe antihyperglycemic derivatives bearing thiazolidinedione fragment based on spectral data. The DFT theory discussed the frontier molecular orbitals (FMOs), chemical reactivity of compounds, and molecular electrostatic potential (MEP) to explain interaction between thiazolidinediones and the biological receptor. α-amylase is known as the initiator-hydrolysis of the of polysaccharides; therefore, developing α-amylase inhibitors can open the way for a potential diabetes mellitus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…In order to assess the binding affinities of 1 – 8 molecules, the pose which had the lowest “ΔE and RMSD” was chosen. To further validate the “ΔE”, the inhibitory constant “Ki” and ligand-efficiency “LE” were computed [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the binding affinities of 1 – 8 molecules, the pose which had the lowest “ΔE and RMSD” was chosen. To further validate the “ΔE”, the inhibitory constant “Ki” and ligand-efficiency “LE” were computed [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sameeh et al again derived different thiazolidin-2,4-dione analogues and evaluated them for their in vitro antioxidant activity using a DPPH radical scavenging assay, taking ascorbic acid as the reference drug. The results of the assay revealed that molecules ao21 and ao22 exhibited a better antioxidant potential than other drugs in the series ( Table 64 , Figure 19 ) [ 92 ].…”
Section: Biological Potential Of the Thiazolidin-24-dione Analoguesmentioning
confidence: 99%
“…These drugs are known to impart activity by insulin sensitization via peroxisome-proliferated activated receptor activation, reducing oxidative stress and conserving islet β-cell function. Despite their high popularity, the use of thiazolidine-2,4-dione is severely limited due to poor selectivity, hepatotoxicity, and carcinogenicity . Among others, one possible way to overcome these limitations is to use a similar core.…”
Section: Introductionmentioning
confidence: 99%